2021
DOI: 10.3390/ijerph19010290
|View full text |Cite
|
Sign up to set email alerts
|

Parent’s Perspective towards Child COVID-19 Vaccination: An Online Cross-Sectional Study in Mexico

Abstract: COVID-19 vaccination programs continue in child populations. Thus, parents’ attitude towards COVID-19 vaccination of their children is crucial for these strategies to succeed. The present study derives from the application of an online COVID-19 Vaccine Acceptance & Hesitancy Questionnaire (COV-AHQ) in which we measure parent’s hesitancy towards children’s vaccination (section 4 of the COV-AHQ) and other significant factors. A logistic regression analysis with backward stepwise method was used to quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…It was shown that whether parents were vaccinated against COVID-19 themselves was related to the acceptance of the COVID-19 vaccine for children. This is in line with past research, as similar findings have been found in different countries as well [ 35 , 62 , 63 ]. It is suggested that parents’ decision of whether to vaccinate their children or not might be partially driven by the same motivations, such as the protection of others, that equally shape their individual vaccination decision.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It was shown that whether parents were vaccinated against COVID-19 themselves was related to the acceptance of the COVID-19 vaccine for children. This is in line with past research, as similar findings have been found in different countries as well [ 35 , 62 , 63 ]. It is suggested that parents’ decision of whether to vaccinate their children or not might be partially driven by the same motivations, such as the protection of others, that equally shape their individual vaccination decision.…”
Section: Discussionsupporting
confidence: 94%
“…Based on the centrality indices, it was shown that, among all variables, collective responsibility displayed the most connections to all other variables. Similar findings have been found in past research as well [ 63 , 64 , 65 ]. Overall, these findings illustrate the determining role of an internal feeling of collective responsibility in vaccine acceptance.…”
Section: Discussionsupporting
confidence: 93%
“…Although there is a plethora of information regarding vaccine uptake and acceptance in adults, little is known about adolescent and parental hesitancy and underlying intentions for COVID-19 vaccines [ 17 , 18 ]. Of the studies that do exist, most examine vaccine acceptance rates and hesitancy, and were carried out before vaccines were authorized for use in adolescents [ 19 , 20 , 21 , 22 , 23 , 24 ]. Additionally, these studies focus on the primary series of vaccination, not booster doses.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the vaccines and vaccination programmes, many preventable diseases have been reduced drastically, and more than two million deaths have been prevented each year. 18 Vaccination mainly targets children, and countries all over the world have taken several measures to enhance vaccination rates among children. 19 Nevertheless, there is a significant rise among parents who refuse to vaccinate their children.…”
Section: Discussionmentioning
confidence: 99%